2007
DOI: 10.1002/job.486
|View full text |Cite
|
Sign up to set email alerts
|

Job design in temporal context: a career dynamics perspective

Abstract: SummaryLeading theories of job design have neglected to incorporate the important context of time into their premises, hindering these theories' explanatory power and utility. We demonstrate how systematically incorporating the context of time, in relation to the specific example of career dynamics, will improve our understanding of job design. We discuss the contribution of time by examining how career dynamics may influence employees' reactions to stimulating jobs and their propensity to craft more stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 71 publications
2
120
2
2
Order By: Relevance
“…As social interaction has become more pervasive and prominent in contemporary work organisations, the importance of social and relational characteristics within job design theory is becoming increasingly recognised (Fried, Grant, Levi, Hadani & Slowik, 2007;Grant & Parker, 2009;Morgeson & Humphrey, 2006;Oldham & Hackman, 2010). A recent meta-analysis by Humphrey et al (2007) found that social characteristics were associated with performance, turnover and satisfaction beyond non-social job properties.…”
Section: Social Resourcesmentioning
confidence: 99%
“…As social interaction has become more pervasive and prominent in contemporary work organisations, the importance of social and relational characteristics within job design theory is becoming increasingly recognised (Fried, Grant, Levi, Hadani & Slowik, 2007;Grant & Parker, 2009;Morgeson & Humphrey, 2006;Oldham & Hackman, 2010). A recent meta-analysis by Humphrey et al (2007) found that social characteristics were associated with performance, turnover and satisfaction beyond non-social job properties.…”
Section: Social Resourcesmentioning
confidence: 99%
“…The vast majority of studies conducted on job crafting are theoretical or qualitative in nature, with few quantitative approaches (Wrzesniewski and Dutton, 2001;Fried et al, 2007;Lyons, 2008;Berg et al, 2010a;Berg et al, 2010b). In this respect, the literature has highlighted the need for more work to be done on the quantitative empirical assessment of job crafting and its link with other study results (Slemp and Vella-Brodrick, 2013).…”
Section: Job Crafting Measurement In the Jd-r Modelmentioning
confidence: 99%
“…Among employees, the attractiveness of earlier promotion increased with the passage of time compared with long-term senior executive positions (Saunders, & Fogarty, 2001). Theoretically, employees are more willing to tolerate non-stimulating jobs if they expect to advance in the near future (Fried, Grant, Levi, Hadani, & Slowik, 2007).…”
Section: Introductionmentioning
confidence: 99%